ATTITUDE OF STUDENTS TOWARDS ENTREPRENEURSHIP THROUGH PEDAGOGY IN NIGERIA: A CRITICAL ANALYSIS AND REFLECTION - ADEDAYO R. AGBONNA; NNALE, MAGAJI; OLALEKAN A. ASHIKIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper looked into pedagogy as a tool for arousing positive attitude toward entrepreneurship. The work considered all federal universities in South-West, Nigeria. The population of the study consisted of 25,443 fourth year students of all federal universities in South-West Nigeria. A sample of 1673 students in their fourth year was used in the study. The study adopted stratified random sampling technique and a structured questionnaire with 6-point Likert scale was used for data collection. Result of the study showed that pedagogy is positively significant to attitude towards entrepreneurship of students of the selected Universities. The study suggests that to promote positive attitude towards entrepreneurship of university undergraduate, innovative pedagogies should be adopted in the teaching of entrepreneurship in the universities in Nigeria. The aforementioned promotes graduate employment and economic growth.